Development of Instruments for Audit Quality Assessment and Control - D. S. Fomina (Учёт. Анализ. Аудит, 2019)
The role of audit firms as independent institutions certifying the reliability of reporting information disclosed by businesses to the wide range of interested parties is currently increasing. At the same time, the audit market is going through a period of crisis because of the decline in prestige of the profession, low profitability, falling user confidence to the results of audit and the lack of national auditing legislation. On the other hand during crisis times the significance of the control over the quality of auditing including the state control goes up. The article systematizes the results of the research on audit quality assessment and control. It also describes methodological approaches to building an effective internal audit control system, provides practical recommendations on how to improve the reporting data of audit firms, identifies conceptual elements of the quality control system and considers the issues of improving the effectiveness of external control. Implementation of the proposals will improve the competitiveness of audit firms in the crisis industry and allow the transition from formal audit control to substantive control.